The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.2147/ppa.s228670
|View full text |Cite
|
Sign up to set email alerts
|

<p>Illness Perceptions, HbA1c, And Adherence In Type 2 Diabetes In Saudi Arabia</p>

Abstract: PurposeLittle is known about predictors of adherence to diabetes medication in Saudi Arabia. This study aimed to investigate whether illness perceptions, beliefs about medicine, and God locus of health control beliefs were associated with adherence to medication and glycaemic control (HbA1c) in Saudi patients with type 2 diabetes (T2D).Patients and methodsA convenience sample of 115 adults with T2D were recruited from a diabetes outpatient clinic. Validated self-reported measures of adherence to medication, il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 52 publications
(94 reference statements)
7
31
0
Order By: Relevance
“…25 In another study conducted by Alyami et al in KSA, only two-thirds (69%) of the adult participants reported good adherence to medication. 26 Based on the EQ-5D-5L, the participants in the current study were relatively healthy in terms of mobility, selfcare, and anxiety/depression. However, approximately one-third of the participants reported at least some problems with pain and discomfort and/or usual care.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 In another study conducted by Alyami et al in KSA, only two-thirds (69%) of the adult participants reported good adherence to medication. 26 Based on the EQ-5D-5L, the participants in the current study were relatively healthy in terms of mobility, selfcare, and anxiety/depression. However, approximately one-third of the participants reported at least some problems with pain and discomfort and/or usual care.…”
Section: Discussionmentioning
confidence: 99%
“… 25 In another study conducted by Alyami et al in KSA, only two-thirds (69%) of the adult participants reported good adherence to medication. 26 …”
Section: Discussionmentioning
confidence: 99%
“…These findings have been supported by subsequent research that found lower HbA 1c was associated with perceived personal control over diabetes 12,13 and more chronic timeline perceptions 14 . Illness perceptions associated with higher HbA 1c include greater consequences, 13 stronger illness identity, 13,15 more cyclical timeline beliefs 4,16 and greater emotional distress 13 …”
Section: Introductionmentioning
confidence: 62%
“…Research has shown that individuals’ illness perceptions are related to health outcomes across a number of chronic conditions 1,2 . In diabetes, illness perceptions have been associated with adherence to self‐care behaviours, 3 glycaemic control as assessed by glycated haemoglobin (HbA 1c ), 4,5 clinic attendance, 6 quality of life, 7 depression, anxiety 8 and mortality 9 …”
Section: Introductionmentioning
confidence: 99%
“…Findings from this study will help inform future interventions aimed at improving adherence to self-care behaviours among Saudi patients with T2D. Associations with medication adherence and glycaemic control have been reported in a separate paper (Alyami, Serlachius, Mokhtar, & Broadbent, 2019).…”
Section: Introductionmentioning
confidence: 67%